Cultural connections between the Eastern European steppe region and the Carpathian Basin in the 5th–7th centuries AD: The origin of the Early Avar Period population of the Trans-Tisza region - Gulyás, Bence (Dissertationes Archaeologicae, 2024)
Extended, completed review of the theses of the PhD dissertation completed under the supervision of Tivadar Vida and submitted to the Archaeological Doctoral Programme, Doctoral School of History, ELTE Eötvös Loránd University, Budapest, in 2023. The dissertation’s primary objective was to investigate the origins of the population that settled in the Trans-Tisza region in the 6th–7th centuries AD. According to prior studies, these populations, unlike the ‘Inner Asian Avars’, may have arrived in the Carpathian Basin from the Eastern European steppe. My research focused on burial practices, comparing the graves discovered in the two regions using quantitative and qualitative methods. The dissertation also includes a comprehensive presentation and analysis of the East European steppe material from the second half of the 5th to the middle third of the 7th century AD.